Coal pyrolysis and its mechanism in indirectly heated fixed-bed with metallic heating plate enhancement. (1st December 2016) - Hu, Erfeng; Zhu, Chuanqiang; Rogers, Kyle; Han, Xue; Wang, Jie; Zhao, Jing; Fu, Xiaoheng
Highlights: The tar yield and light fraction increased then decreased when increasing the number of plates. Working mechanism of metallic plates was proposed and verified by an in-house design. An excessive number of plates resulted in aggravating the cracking of primary products. Abstract: A metallic plate has been devised to enhance the heat transfer; this in turn increases the yield and quality of coal tar (Zhang et al., 2013). This work is devoted to investigating the pyrolysis of Yilan subbituminous coal and developing a working mechanism for an indirectly heated fixed bed reactor with different number of metallic plates. Increasing the number of metallic heating plates enhanced the heat transfer from the high-temperature reactor wall to the low-temperature central coal layer and thereby shortened the reaction time. Meanwhile, the yields of tar and light fraction were increased then decreased. The results of the pressure drop experiment demonstrated that the metallic plates weakened dense stacks of coal particles and raised the particle interstices, and therefore lowered the gas diffusion resistance. It verified that many gaseous pyrolysis products escaped from the central low-temperature coal layer, indicating the suppressed secondary reactions to the primary products. When the number of plates was 8, the correspondingly added high-temperature surface was 113%; it achieved the optimal matching between the secondary reactions of pyrolysis products and the fields of the temperature as well as the gas flow inside the reactor, and it also had the highest tar yield (6.60 wt.% dry basis) and the maximum content of light tar (below the boiling points of 360 °C) of 76.4 wt.% and C4–C9 components of 43.52 wt.%. The BET results showed that the char had the biggest surface area and volume for this case with 8 plates. Consequently, adding suitable metallic plates into the indirectly heated fixed bed reactor obviously enhances the heat transfer and also achieves higher yield and quality of tar.